"Future-proof your Degree": Embedding sustainability and employability at Nottingham Business School (NBS). Issue 8 (18th July 2019) - Winfield, Fiona; Ndlovu, Tabani
Abstract : Purpose: The purpose of this paper is to present a case study of how a UK business school has explicitly linked sustainability to employability and embedded these into all levels of its undergraduate and postgraduate degree portfolio. Design/methodology/approach: This case study features Nottingham Business School's (NBS's) journey of linking sustainability with employability to achieve the University's strategic objectives and help deliver on the sustainable development goals (SDGs). After reviewing all courses, a cross-school approach was adopted in re-designing the curriculum, first at undergraduate and later postgraduate level. Partnerships, both internal and external were developed, involving the employability and enterprise teams, the University's students and alumni, local employers, local authorities and businesses and charities. Feedback from graduates is included. Findings: When NBS introduced new undergraduate modules in 2012, there was resistance with concerns over already crammed curricula and the perceived irrelevance of sustainability. This changed as students realised that an understanding of sustainability was benefiting them at interviews and adding value to their employers. While it cannot be proved that increased self-awareness and sustainability literacy have a direct effect on graduate prospects (as measured by the Destinations of Leavers from Higher Education survey), NBS has seen the percentage of students in graduate level employment and/or study increase from 71 to 89.6 per cent over the past five years. Originality/value: Linking sustainability to employability, and embedding these in the curriculum, should benefit any institution, its students, employers and society, and can be replicated anywhere in the world.